Developing framework toward one health approach: Relevance and future implications - Suraj Kapoor (Wolters Kluwer Medknow Publications, 2023)
Against a constant background of recognized infections, epidemics of new and old infectious diseases periodically emerge, greatly magnifying the global burden of emerging and re-emerging diseases. The emergence/re-emergence of these diseases is related to multifaceted factors, such as viral recombination and mutation, leading to more infectious and adaptive strains, industrialization and urbanization, and human activities such as deforestation creating a more permissive environment for vector-host interaction. A better knowledge of the causes and consequences of certain human activities, lifestyles, and behaviors in ecosystems is crucial for a rigorous interpretation of disease dynamics and to drive public policies. This article highlights the factors associated with emergence and re-emergence and in turn the importance and implementation of the One Health approach. Health-care professionals can prevent and control antimicrobial resistance by prescribing and dispensing antibiotics as per the laid down guidelines and indications. Sentinel surveillance at the point of entry should be strengthened. Successful One Health approaches require intersectoral coordination, with a team approach despite functioning in different sectors or domains. It is proposed that government and policy-makers should take scientific decisions about the creation of epidemiological surveillance centers at the district level on the concept of One Health. It should have facilities and infrastructure for ecosystem surveillance, namely air, water, soil, flora, and fauna, monitoring as well as investigation of the outbreak. Equally important is to empower the community and family members about the One Health concept and the matters concerned.